PELAKSANAAN ANTENATAL CARE DENGAN 10 T DIPUSKESMAS MUNGKUR AGUNG KECAMATAN KELUA: Implementation of Antenatal Care with 10 T at the Mungkur Agung Health Center, Kelua Sub-District - Lestari, Sri; Dona, Sismeri; Hestiyana, Nita (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
Maternal and child health is a priority for health development in Indonesia. The implementation of Ante Natal Care with 10 T in pregnant women affects the results of early detection of risks and complications during pregnancy. This cause of maternal death shows that maternal death can be prevented if the coverage of services is accompanied by good quality service. The purpose of the study was to determine the Implementation of Antenatal Care with 10 T at the Mungkur Agung Health Center, Kelua District. This research method with quantitative descriptive, with a population of all pregnant women at 20 weeks gestational age and over trimester II, III with a total sampling technique, namely pregnant women totaling 38 people Results: It was found that the implementation of ANC with 10 T according to the standard was (97.37%), %) and there was 1 (2.63%) pregnant women who in the implementation of ANC did not meet the 10 T standard.